Peningkatan Prestasi Belajar Matematika Persamaan Garis Lurus dengan Model Pembelajaran Discovery Learning pada Siswa Kelas VIII-C SMP Negeri 1 Grogol Kabupaten Kediri - Sujoko, Nanang Andi (Jurnal Simki Postgraduate, 2023)
To make changes in improving the quality and quality of teacher education is very important, because the teacher is the front person whose job is to transfer knowledge to students. For this reason, a learning strategy is needed that is carried out by the teacher and is very dependent on the creativity of the teacher himself in conveying the contents of the material to students. Learning models that do not involve students will reduce student learning interest, so that learning achievement will also decrease. A learning model that places more emphasis on student activity is a teaching and learning model that prioritizes the active role of students, both physically, mentally and socially. Discovery learning is a model for developing an active way of learning by self-discovery, self-investigation, so the results obtained will be loyal and long-lasting in memory. Through discovery learning, students can also learn to think analytically and try to solve their own problems. The results of this study are 1) The Discovery Learning learning model can increase student achievement activities in Class VIII-C at SMP Negeri 1 Grogol Kediri Regency Even Semester in the 2018/2019 Academic Year. 2) The Discovery Learning learning model can improve student achievement as indicated by the increase in the percentage of classical mastery and class average grades. In cycle 1, the percentage of classical completeness was 58.33% with an average grade of 66.22. In cycle 2, the percentage of classical mastery was 72.2% with an average grade of 74.86. In cycle 3 the percentage of classical mastery was 86.11% with an average grade of 82.52